Presidential years 2012-2017 - Mukherjee, Pranab (New Delhi Rupa, 2021)
The Presidential Years offers a fascinating account of how one of the country$1 (Bs most respected veteran politicians reshaped the functioning of Rashtrapati Bhavan and responded to tumultuous events as the country$1 (Bs first citizen, leaving behind a legacy that will be hard to match. Pranab Mukherjee became President of India after having spent several decades in politics, and there was great speculation over how he would approach his new bipartisan role after having been associated with a political party for so many years of his life. By the time he had served his term, Mukherjee had won the respect and admiration of people from across the political spectrum, including those who were his rivals when he was a political figure. He had the occasion to work with two prime ministers, belonging to two parties who were (and are) fiercely opposed to each other, and he managed to do so with aplomb.s
Keywords: President-India; Mukherjee, Pranab-Biography